Nephrologist Interventions to Avoid Kidney Replacement Therapy in Acute Kidney Injury - Jonathan S. Chávez-Íñiguez; Pablo Maggiani-Aguilera; Christian Pérez-Flores; Rolando Claure-Del Granado; Andrés E. De la Torre-Quiroga; Alejandro Martínez-Gallardo González; Guillermo Navarro-Blackaller; Ramón Medina-González; Jochen G. Raimann; Francisco G. Yanowsky-Escatell; Guillermo García-García (Karger Publishers, 2021)
Background: Based on the pathophysiology of acute kidney injury (AKI), it is plausible that certain early interventions by the nephrologist could influence its trajectory. In this study, we investigated the impact of 5 early nephrology interventions on starting kidney replacement therapy (KRT), AKI progression, and death. Methods: In a prospective cohort at the Hospital Civil of Guadalajara, we followed up for 10 days AKI patients in whom a nephrology consultation was requested. We analyzed 5 early interventions of the nephrology team (fluid adjustment, nephrotoxic withdrawal, antibiotic dose adjustment, nutritional adjustment, and removal of hyperchloremic solutions) after the propensity score and multivariate analysis for the risk of starting KRT (primary objective), AKI progression to stage 3, and death (secondary objectives). Results: From 2017 to 2020, we analyzed 288 AKI patients. The mean age was 55.3 years, 60.7% were male, AKI KDIGO stage 3 was present in 50.5% of them, sepsis was the main etiology 50.3%, and 72 (25%) patients started KRT. The overall survival was 84.4%. Fluid adjustment was the only intervention associated with a decreased risk for starting KRT (odds ratio [OR]: 0.58, 95% confidence interval [CI]: 0.48-0.70, and p ≤ 0.001) and AKI progression to stage 3 (OR: 0.59, 95% CI: 0.49-0.71, and p ≤ 0.001). Receiving vasopressors and KRT were associated with mortality. None of the interventions studied was associated with reducing the risk of death. Conclusions: In this prospective cohort study of AKI patients, we found for the first time that early nephrologist intervention and fluid prescription adjustment were associated with lower risk of starting KRT and progression to AKI stage 3.